SOCIAL POLICY IN THE REGIONS: MANAGEMENT OF SOCIAL PROJECTS IN ORGANIZATION - Natalia Nikolayevna Voroshilina (Современная наука и инновации)
Results of a research are reflected in article I aim which determination of the actual results of the social projects realized in TTsSON of the Central district of Minsk, their ratio with stated purposes and determination of tendencies and dynamics of changes of level of living of the population as a result of implementation of social projects is.